2023
DOI: 10.1021/acs.inorgchem.3c02662
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenyl-Substituted Imidazo[4,5-f][1,10]phenanthroline Rhenium(I) Complexes with Record-High Triplet Excited-State Lifetimes at Room Temperature: Steric Control of Photoinduced Processes in Bichromophoric Systems

Katarzyna Choroba,
Mateusz Penkala,
Joanna Palion-Gazda
et al.

Abstract: Photochemical applications based on intermolecular photoinduced energy triplet state transfer require photosensitizers with strong visible absorptivity and extended triplet excited-state lifetimes. Using a bichromophore approach, two Re(I) tricarbonyl complexes with 2-showing extraordinary long triplet excited states at room temperature (>1000 μs) were obtained, and their ground-and excited-state properties were thoroughly investigated by a wide range of spectroscopic methods, including femtosecond transient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 93 publications
2
6
0
Order By: Relevance
“…Furthermore, we believe that this Coulomb approach has a less pronounced effect on the individual energy levels of the sensitizer and the mediator compared to the spacer-dependent effects observed with covalently linked bichromophores. 45–47 While ionic interactions were considered in (photo)catalysis 48–53 and self-assembled upconversion systems 54–56 previously, these interactions have not been exploited for mediated sTTA-UC systems in homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we believe that this Coulomb approach has a less pronounced effect on the individual energy levels of the sensitizer and the mediator compared to the spacer-dependent effects observed with covalently linked bichromophores. 45–47 While ionic interactions were considered in (photo)catalysis 48–53 and self-assembled upconversion systems 54–56 previously, these interactions have not been exploited for mediated sTTA-UC systems in homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
“…In the design of photoactive systems, whether they are for photocatalytic, environmental sensing, photodynamic therapy, or photovoltaic applications, , the light-harvesting molecule or moiety plays a crucial role in the overall functionality and efficiency of the system. The molecular design is influenced by the desired photophysical properties, be they achieving ligand loss such as in the case of photoCORMS , and in some photocatalysts, , unidirectional electron transfer to a specific acceptor moiety , or the reduction of charge recombination rates and the creation of long-lived excited states. Whatever the desired photophysical behavior, a fundamental understanding of the photophysical and photochemical processes involved is vital to the photosensitizer’s design.…”
Section: Introductionmentioning
confidence: 99%
“…One means by which this can be achieved is through the incorporation of large aromatic chromophores. This can facilitate a population of triplet ligand-centered ( 3 LC) states, which typically have much longer lifetimes than their triplet metal-to-ligand charge-transfer ( 3 MLCT) state counterparts due to their localization away from the metal center. ,, For example, a recent study by Choroba et al investigated pyrene-substituted Re­(I) complexes with room-temperature phosphorescent lifetimes greater than 1000 μs . Similarly, a study by Wenger and co-workers showed that naphthalene was able to function as a triplet reservoir in an Ir­(III) complex, leading to lifetimes of 72.1 μs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aim of this work was to explore the impact of the triimine skeleton (terpy and dtpy) and substituents (thiophene, bithiophene, and EDOT) on the photophysical properties of Ir(III) complexes. Recently, some efforts have been made to understand the structure-property correlation in rhenium(I), platinum(I), gold(I), cobalt(II), and copper(II) [20][21][22][23][24][25][26] complexes by introducing the R substituent in the 4 ′ -position of the terpy and/or dtpy rings. However, to the best of our knowledge, [IrCl 3 (L)] complexes incorporating terpy (ligands L 1 -L 3 ) and dtpy derivatives (ligands L 4 -L 6 ) are quite rare and will be reported here for the first time (see Table S15).…”
Section: Introductionmentioning
confidence: 99%